Afro-descendants and Social Stratification in Mexico. New Evidence from the 2015 Intercensal Survey in Mexico - Torre-Cantalapiedra, Eduardo; Sánchez-Soto, Gabriela (Papeles de Población; Vol. 25 Núm. 100 (2019): Papeles de Población, 2019)
The 2015 Intercensal Survey marks the first time African descent self-identification was included on a nationally representative survey in Mexico. Before that, there were no nation-wide official counts of the Afro-Mexican population. Previous research has found that Afro-Mexicans have lower socioeconomic status and more limited access to economic opportunity relative to the rest of the population, however, this question has not been explored at the national level. In this paper we use ordinal logistic regression models to examine the effect of being Afro-descendant on the educational and occupational status of Mexicans. Contrary to expectations, our results show that, at the national level, there is no evidence that the self-identified Afro-Mexican population has a lower socioeconomic status than other Mexicans. This contradictory result may be attributed to a higher likelihood of Afro-descendant self-identification among more educated people, and lower among the most disadvantaged, particularly in areas where Afro-Mexicans are less represented.